A Novel Kinetic Method to Measure Apparent Solubility Product of Bulk Human Enamel - Hassanali, Linda; Wong, Ferranti S.; Lynch, Richard J. M.; Anderson, Paul (Frontiers in Physiology, 2017)
Introduction: Tooth enamel mineral loss is influenced by its solubility product value, which is fundamental to the understanding of de- and remineralization resulting from a carious or erosive challenge. Published pKsp values for human enamel and hydroxyapatite range from 110 to 126 suggesting a heterogeneous nature of enamel solubility. However, this range of values may also result from the variety of methods used, e.g., some authors reporting values for suspensions of enamel powder and others for bulk enamel. The aim of this study was to develop a method to measure the solubility of bulk human enamel under controlled in vitro conditions simulating demineralization behavior of enamel within the oral environment using scanning microradiography (SMR). SMR was used to monitor real-time changes in enamel demineralization rates at increasing calcium concentrations in a caries simulating demineralization solution until the concentration at which thermodynamic equilibrium between enamel and solution was achieved. Method: 2 mm thick caries free erupted human enamel slabs with the natural buccal surfaces exposed were placed in SMR cells exposed to circulating caries-simulating 2.0 L 0.1 M pH = 4.0 acetic acid, at 25°C. SMR was used to continuously measure in real-time the decrease in mineral mass during the demineralization at 5 different points from on each slab. Demineralization rates were calculated from a linear regression curve of projected mineral mass against demineralization time. Changes in the demineralization rates were monitored following a series of successive increases in calcium (and phosphate at hydroxyapatite stoichiometric ratios of Ca:P 1.67) were added to the demineralizing solution, until demineralization ceased. The pH was maintained constant throughout. Results: Demineralization halted when the calcium concentration was 30 mM. At higher calcium concentrations, mineral deposition (remineralization) occurred. By comparison with results from speciation software calculations for the calcium phosphate ternary system, this result suggests that the bulk solubility product of enamel (pKspBEnamel) under the conditions used is 121. Discussion: The apparent pKspBEnamel under these conditions was higher than many previous reported values, and much closer to those previously reported for HAp. However, this is a bulk value, and does not reflect that enamel is a heterogeneous material, nor the influence of ionic inclusions.